2010
DOI: 10.2174/156720510791383859
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Oligomers Decrease Hippocampal Spontaneous Network Activity in an Age-Dependent Manner

Abstract: Soluble amyloid beta (Abeta) oligomers might trigger early cognitive impairment in Alzheimer's Disease (AD) through the impairment of proper neuronal network function. We have recently shown that the short sequence Abeta(25-35) affects the spontaneous activity in hippocampal slices, when was added to the bath, at high nanomolar concentrations. In the present study, we aimed to characterize the effects of the oligomerized full length sequence Abeta(1-42) on the spontaneous network activity in the CA1 hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 83 publications
(133 reference statements)
3
28
0
Order By: Relevance
“…Spontaneous prefrontal network recordings in slices showed low-voltage neuronal activity that includes a broad range of frequency components (Figure 1; n = 10; meaning 10 slices obtained from 10 animals, with only one slice per animal). As previously shown for other neuronal networks [3437], this activity is reduced by the application of 30 nM A β (Figure 1, representative traces and power spectra). Analysis of the integrated power (from 1 to 120 Hz) showed a significant reduction of the prefrontal spontaneous network activity 60 min after A β application (to 63.2 ± 8.5% of basal activity, p < 0.05; n = 10) (Figure 1, inset bar graph).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Spontaneous prefrontal network recordings in slices showed low-voltage neuronal activity that includes a broad range of frequency components (Figure 1; n = 10; meaning 10 slices obtained from 10 animals, with only one slice per animal). As previously shown for other neuronal networks [3437], this activity is reduced by the application of 30 nM A β (Figure 1, representative traces and power spectra). Analysis of the integrated power (from 1 to 120 Hz) showed a significant reduction of the prefrontal spontaneous network activity 60 min after A β application (to 63.2 ± 8.5% of basal activity, p < 0.05; n = 10) (Figure 1, inset bar graph).…”
Section: Resultssupporting
confidence: 83%
“…This latter effect might contribute to the A β -induced action potential desynchronization in the hippocampus that contributes to the inhibition of its neural network activity [45]. Aside from the changes in cell excitability, the inhibition of neural network activity induced by A β has also been related to a reduction in both excitatory [34, 37, 47, 48] and inhibitory [47, 48] synaptic transmission. In fact, these findings are consistent with the observation that A β reduced cholinergic modulation of the inhibitory transmission in the PFC [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paradoxical situation might be explainable given the sophisticated pathophysiology of the septohippocampal system and the heterogeneity, that is, dualistic theory of hippocampal theta activity, that is, hippocampal theta being differentiated into atropine-insensitive type I and atropine-sensitive type II theta [40, 60]. It has been reported that A β can modulate cholinergic and glutamatergic neurons in the septohippocampal system [6164] and that the presence of A β in both the medial septum and the hippocampus can dampen theta rhythm in vitro and in vivo [62, 6569] which is associated with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%